A replacement name for the genus-group name NannaBirket-Smith, 1965 (Erebidae: Arctiinae: Syntomini) - de Prins, Willy (Zootaxa, 2021)
In the fly family Scathophagidae (Diptera), the genus Nanna Strobl, 1894 was introduced as “(D. Nanna Becker) flavipes Fall. Zett. 2059, 6332, SS.11! Becker!” (Strobl 1894: 78), with Cordylura flavipes Fallén, 1819 as its type species. See Michelsen (2001: 323–326) for correct authorship and validity of the name Nanna Strobl, 1894 as senior synonym of names proposed by Becker (1894) in the same year.